KEMAMPUAN SISWA KELAS X SMA N 06 OKU MENEMUKAN NILAI AGAMA DALAM CERITA PENDEK4 KOPIAH KARYA FAQIH SULTHAN - Rita Nilawijaya (Universitas Andalas, 2019)
Researchers examine the Ability of High School Students of SMA N 06 OKU Finding Value of Religion in Short Story 4 Kopiah Karya Faqih Sulthan. The formulation of the problem in this research is how the ability of high school students of SMA N 06 OKU find the value of religion in short story 4 Kopiah by Faqih Sulthan. This study aims to describe the ability of students of grade X SMA N 06 OKU to find the value of religion in short story 4 Kopiahkarya Faqih Sulthan.Manfaat this research is expected to give description about religious values in short stories, and can be useful for teachers, students, readers, and researchers. The method that researchers use is descriptive method. Data collection techniques are test techniques. The sample in this study amounted to 36 students. The result of the research on the ability of the students of grade X of SMA Negeri 06 OKU find the religious value in the short story that there are students who can find the religion value on the element of aqidah with the value of 11-20 as many as 34 or 94.4%, with the value of 21-40 as many as 32 people or 88.9% the value of 21-40 as many as 10 people or 27.8%, with a grade point average of 68.9. Based on the Kreteria Complete Minimal value of Indonesian language in SMA N 06 OKU with a value of 75, then the students of class X.2 otherwise have not been able to find the value of religion in the short story 4 Kopiah works Faqih Sulthan.Keywords: ability, religion value, short story